Antiviral therapy for chronic hepatitis C: is there a time to change existing standards? - D. T. Abdurakhmanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze efficacy of antiviral therapy of various duration in patients with chronic hepatitis C (CHC).Original positions of the report. According to published data viremia dynamics has important prognostic value during treatment, which allows to consider it as one of important factors determining duration and efficacy of treatment along with virus genotype. Poor efficacy of the latter, especially at patients with the 1-st HCV genotype, high cost and risk of the serious undesirable effects cause necessity to individualize antiviral therapy at CHC, improve risk/benefit ratio.Conclusion. At CHC patients with the rapid virologic response (absence of viremia at the 4-th week) it is possible to limit duration of treatment by pegilated interferon and ribavirin in the case of the 1-st HCV genotype to 24 wks, in the case of the 2 and 3-rd genotypes to 12–16 wk. In patients with the 3-rd HCV genotype without rapid virologic response and in patients with the 1-st HCV genotype and slow virologic response treatment probably should be prolonged to 48 and 72 wks respectively.